Plasma carotenoid levels in passerines are related to infection by (some) parasites - Figuerola, Jordi; López, Guillermo; Soriguer, Ramón (Frontiers in Ecology and Evolution, 2014)
Plumage coloration plays an important role in intra and inter-sexual competition in birds. Many of the yellow, orange or red colours present in birds are carotenoid dependent. Carotenoids can not be synthetized de novo by birds and consequently should be obtained through their diet, and access to carotenoids may differ between individuals and species. In addition to ornamentation, carotenoids are important for bird physiology and it has been proposed that a trade-off in their allocation to these two functions occurs. Under this scenario parasites may play a central role in maintaining the honesty of plumage as a signaling system by increasing the demands for carotenoids for infection or damage control and/or by reducing carotenoid absorption in the intestines. We analyzed the relationship between (1) carotenoid concentrations in plasma and (2) blood and intestinal parasite richness and abundance in 22 species of passerines sampled in spring. Loads of different groups of parasites were unrelated so conclusions drawn from examining a particular group of parasites cannot be extrapolated to the whole community of pathogens and parasites inhabiting a host. At intraspecific level plasma carotenoid concentration was negatively related to the richness of intestinal parasites and the abundance of some groups of intestinal parasites, at interspecific level plasma carotenoid concentration was negatively related with the abundance of intestinal parasites. No relationship at intra- nor interpecific level was found between carotenoids and blood parasites. The results suggest that intestinal parasites play an important role in the evolution and maintenance of carotenoid-derived sexually selected ornamentations probably through a negative impact on the uptake of carotenoids at the gut.